The Relationship Between the Shape of the Spine and the Width of Linea Alba in Children Aged 6–9 Years. Case-Control Study - Zmyślna, Anna; Żurawski, Arkadiusz; Rosiński, Tomasz; Pogorzelska, Justyna; Śliwiński, Zbigniew; Śliwiński, Grzegorz; Kiebzak, Wojciech (Frontiers in Pediatrics, 2022)
Introduction Civilization development coupled with contemporary lifestyle leads to a systematic increase in postural disorders. An analysis of factors that may provoke postural disorders indicates that such a stimulus may be the diastasis of the rectus abdominis muscles. Moreover, abnormal activity of the rectus abdominis muscles may affect balance disorders through reduced spinal stabilization and disturbed body statics. There is an increase in body posture abnormalities between the ages of 6 and 9 related to new school duties. Purpose of the Study The purpose of the study was to evaluate the relationship between the shape of the spine and the width of the linea alba in children aged 6–9 years. Material and Method The study was designed to evaluate parameters determining the shape of the spine, and the width of the linea alba in healthy children aged 6–9 years. The study participants were divided into two groups based on the width of the linea alba. The study group with the width of the linea alba >10 mm and the control group with the width of the linea alba ≤ 10 mm. The study group were included 37 children and the control group 24 children. The examination of the linea alba width was performed by a radiology specialist using a linear transducer and SAOTE- My Lab Classc-type ultrasound at rest and during contraction of the rectus abdominis muscles. Parameters describing the shape of the spine were measured using the Diers Formetric 4D system: trunk inclination, trunk imbalance, pelvis tilt, pelvic torsion, kyphotic apex, lordotic apex, kyphotic angle, lordotic angle, rotation angle, trunk torsion, lateral deviation. The obtained results were statistically analyzed using a Paired t test for comparison of differences between the results in the study and control groups and Pearson's test to assess the correlation between the width of the linea alba and parameters describing spinal alignment. Results In both groups, the parameters describing the shape of the spine did not differ from the norms accepted as typical for the age norm. The only statistically significant difference between the study and control group concerned the trunk inclination, which was negative in the study group, signifying a shift of the entire spine axis backwards beyond the vertical. Conclusions There is a correlation between the shape of spine and the width of the linea alba in terms of selected parameters determining the body posture in the sagittal plane, which concern: the position of the lumbar lordotic apex, trunk inclination and the depth of the lumbar lordotic angle. The width of the linea alba is not explicitly related to abnormalities of pelvic and spinal alignment in the frontal and transverse planes.